PROSES PEMBELAJARAN PENDIDIKAN AGAMA ISLAM MULTIKULTURAL BERBASIS TASAWUF (STUDI FENOMENOLOGIS PADA KEGIATAN SELOSOAN DI PESANTREN NGALAH) - Uswatun Chasanah (Journal Multicultural of Islamic Education, 2022)
The purpose of this study was to determine the learning process of multicultural Islamic education based on Sufism. This type of research is descriptive-qualitative with a phenomenological approach that is used to understand the essence of a series of events involving the experience of people who actually experience the phenomenon. Data collection techniques through participatory observation, in-depth interviews, and document analysis. and data analysis using phenomenological analysis. The result of the research is the learning process in selosoan uses two approaches, namely 1) with a Sufism approach through the practice of ritual worship which is reflected in the practice of prayer, remembrance, tausiyah and prayer as an effort to increase and develop faith and foster spirituality. 2) religious education with multicultural insight which is carried out in a dialogical manner which is reflected in social actions carried out by involving several interfaith communities.